Analisis Kelayakan Usaha dan Nilai Tambah Olahan Kedelai Menjadi Tempe pada UMKM Super Murni Kecamatan Bekasi Selatan Kota Bekasi - Rahmadinanti, Dwi Utami; Muharam, Muharam; Yusiana, Ekalia (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Agriculture plays an important role in providing food sources that support the survival of society. The growth of the agro-industrial sector not only provides economic benefits for businesses but also contributes to improving the welfare of farmers and the sustainability of the agricultural sector as a whole. Soybean as a multifunctional crop can be utilised to make various culinary delights including tempeh, a traditional Indonesian food. The main objective of this study, conducted by Super Murni MSME, is to evaluate the added value contributed in one production and the business feasibility of tempe production at Super Murni MSME. By considering prices, inputs, and outputs, a value-added analysis approach using the Hayami method and R/C ratio is needed to determine the feasibility of the company. The results showed that the added value required by Super Murni MSMEs in one production of tempe geblekan reached IDR 23,072 or around 61%, using the value-added ratio, the margin obtained reached IDR 21,348 for tempe geblekan. As for tempe lonjoran, the added value is IDR 35,372 or around 71%, with a profit of IDR 31,205. The calculation of business feasibility using the R/C ratio shows a figure of 1.25 for tempe geblekan which indicates that the Company can develop based on the R/C ratio criteria and an R/C ratio of 1.00 for tempe lonjoran which indicates that this business can be developed because it does not experience losses or profits (break-even) to be operated.